Neuroimaging phenotypes of CSF1R‐related leukoencephalopathy: Systematic review, meta‐analysis, and imaging recommendations. (22nd December 2021) - Mickeviciute, Goda‐Camille; Valiuskyte, Monika; Plattén, Michael; Wszolek, Zbigniew K.; Andersen, Oluf; Danylaité Karrenbauer, Virginija; Ineichen, Benjamin V.; Granberg, Tobias
Abstract: Colony‐stimulating factor 1 receptor ( CSF1R )‐related leukoencephalopathy is a rare but fatal microgliopathy. The diagnosis is often delayed due to multifaceted symptoms that can mimic several other neurological disorders. Imaging provides diagnostic clues that help identify cases. The objective of this study was to integrate the literature on neuroimaging phenotypes of C SF1R ‐related leukoencephalopathy. A systematic review and meta‐analysis were performed for neuroimaging findings of CSF1R ‐related leukoencephalopathy via PubMed, Web of Science, and Embase on 25 August 2021. The search included cases with confirmed CSF1R mutations reported under the previous terms hereditary diffuse leukoencephalopathy with spheroids, pigmentary orthochromatic leukodystrophy, and adult‐onset leukoencephalopathy with axonal spheroids and pigmented glia. In 78 studies providing neuroimaging data, 195 cases were identified carrying CSF1R mutations in 14 exons and five introns. Women had a statistically significant earlier age of onset ( p = 0.041, 40 vs 43 years). Mean delay between symptom onset and neuroimaging was 2.3 years. Main magnetic resonance imaging (MRI) findings were frontoparietal white matter lesions, callosal thinning, and foci of restricted diffusion. The hallmark computed tomography (CT) finding was white matter calcifications. Widespread cerebral hypometabolism and hypoperfusion were reported using positron emission tomography and single‐photon emission computed tomography. In conclusion, CSF1R ‐related leukoencephalopathy is associated with progressive white matter lesions and brain atrophy that can resemble other neurodegenerative/‐inflammatory disorders. However, long‐lasting diffusion restriction and parenchymal calcifications are more specific findings that can aid the differential diagnosis. Native brain CT and brain MRI (with and without a contrast agent) are recommended with proposed protocols and pictorial examples are provided. Abstract :